Avaliação da solidificação e da interface de reação de juntas soldadas de ligas Sn-Bi E Sn-Bi-In em substratos de cobre e níquel - Leal, Jaderson Rodrigo da Silva (Universidade Federal de São Carlos, 2024)
In order to explore the potential of Sn-Bi-In alloy utilization in soldering operations, the present proposal analyzed the influence of In addition (10 wt.%) on solidification, microstructure, wettability, tensile properties, and interfacial characteristics of the Sn-40%Bi (wt.%) alloy soldered on Cu and Ni substrates. Various techniques were employed for this study, including CALPHAD, DSC, SEM, XRD, wettability tests, and tensile tests. Evaluating the solidification of the Sn-40%Bi-10%In alloy can be quite complex due to the different possible reactions during solidification. In this regard, microstructure assessment was conducted via three processing routes: graphite mold, centrifugation in copper mold, and slow cooling in a goniometer. The microstructure consisted of the following phases: β-Sn, Bi, and InBi. While faster cooling facilitated the formation of Bi+BiIn clusters, a coarse lamellar microstructure was observed under slower solidification conditions. Contact angles were measured against copper and nickel: 24.5±4.7° and 26.2±6.0°, respectively. The formation and growth of alloy/Cu and alloy/Ni reaction layers were also evaluated under different aging conditions of the as-soldered joints (100 °C, 110 °C, and 120 °C for 120 h, 240 h, and 360 h), simulating usage conditions, revealing the influence of In in reducing the reaction layer growth. In the Alloy/Cu system, a 15 days aging period promoted a 495% increase in the reaction layer, whereas for the Ni substrate, the increase was 51%. Lastly, the adhesion of the soldered alloy/Cu and alloy/Ni couples was analyzed through tensile tests. It was observed that the alloy/Ni coupled exhibited better adhesion. The average maximum force for the alloy/Ni system was 163.9 N, while for the alloy/Cu was 133.5 N.
Evaluation of solidification and reaction interface of Sn-Bi and Sn-Bi-In solder alloys in copper and nickel pads
Keywords: Ligas Sn-Bi-In; Solidificação; Molhabilidade; Interface de reação; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA